ACTION OF LEPTIN ON BONE AND ITS RELATIONSHIP TO MENOPAUSE - Petzel, Martin (Biomedical papers, 2007)
Backround: Leptin a cytokine protein secreted by adipose tissue raises considerable interest as a potential mediator of the protective effects of fat mass on bone tissue. After menopause heavier women conserve bone mass better than those with lower body weight. The protective effect of obesity on bone mass has been ascribed to a high body fat content. As Leptin levels reflect the body fat content it has emerged as a possible mediator of these protective effects.Methods: A search of the available literature focused on the role of leptin on bone tissue.Results: Both peripheral and central action of leptin on bone metabolism have been proposed. In vitro and in vivo evidence supports the hypothesis that leptin can act directly or indirectly on bone remodelling by modulating both osteoblast and osteoclast activities. However, studies in humans have not yet been able to confirm these actions possibly because of the shifting balance between stimulatory direct action and suppressive indirect action of leptin on bones via the hypothalamus. The effects of oestrogen decline and deficiency during natural or artificially induced menopause and administration of hormone replacement therapy has on leptin production remains controversial. Various studies have shown differences in leptin values in pre- and postmenopausal women. The existing clinical data on this issue are discordant.Conclusion: Larger clinical studies are necessary to clarify leptin's role in vivo and to assess the contribution of the central and peripheral role of leptin in the overall maintenance of bone turnover in human beings.
Keywords: Leptin/Bone/Osteoporosis/Menopause/Hormone replacement therapy